Infarct Growth despite Successful Endovascular Reperfusion in Acute Ischemic Stroke: A Meta-analysis - Bala, F.; Ospel, J.; Mulpur, B.; Kim, B.J.; Yoo, J.; Menon, B.K.; Goyal, M.; Federau, C.; Sohn, S.-I.; Hussain, M.S.; Almekhlafi, M.A. (American Journal of Neuroradiology, 2021)
BACKGROUND: Infarct volume inversely correlates with good recovery in stroke. The magnitude and predictors of infarct growth despite successful reperfusion via endovascular treatment are not known.PURPOSE: We aimed to summarize the extent of infarct growth in patients with acute stroke who achieved successful reperfusion (TICI 2b–3) after endovascular treatment.DATA SOURCES: We performed a systematic review and meta-analysis by searching MEDLINE and Google Scholar for articles published up to October 31, 2020.STUDY SELECTION: Studies of >10 patients reporting baseline and post-endovascular treatment infarct volumes on MR imaging were included. Only patients with TICI 2b–3 were included. We calculated infarct growth at a study level as the difference between baseline and follow-up MR imaging infarct volumes.DATA ANALYSIS: Our search yielded 345 studies, and we included 10 studies reporting on 973 patients having undergone endovascular treatment who achieved successful reperfusion.DATA SYNTHESIS: The mean baseline infarct volume was 19.5 mL, while the mean final infarct volume was 37.5 mL. A TICI 2b reperfusion grade was achieved in 24% of patients, and TICI 2c or 3 in 76%. The pooled mean infarct growth was 14.8 mL (95% CI, 7.9–21.7 mL). Meta-regression showed higher infarct growth in studies that reported higher baseline infarct volumes, higher rates of incomplete reperfusion (modified TICI 2b), and longer onset-to-reperfusion times.LIMITATIONS: Significant heterogeneity among studies was noted and might be driven by the difference in infarct growth between early- and late-treatment studies.CONCLUSIONS: These results suggest considerable infarct growth despite successful endovascular treatment reperfusion and call for a faster workflow and the need for specific therapies to limit infarct growth.EVTendovascular treatmentmTICImodified TICI